Challenging Aspects to Precise Health Strategies in Native Hawaiian and Other Pacific Islanders Using Statins - Ligia M. Watanabe; Lucia A. Seale (Frontiers Media S.A., 2022)
Cardiometabolic disorders (CD), including cardiovascular disease (CVD), diabetes, and obesity, are the leading cause of health concern in the United States (U.S.), disproportionately affecting indigenous populations such a Native Hawaiian and Other Pacific Islanders (NHOPI). Dyslipidemia, a prevalent risk factor for the development and progression of CVD, is more prone to occur in NHOPI than other populations in the U.S. High-intensity statin therapy to reduce low-density lipoprotein cholesterol is associated with the prevention of CVD events. However, significant side-effects, such as muscle disorders, have been associated with its use. Different ethnic groups could experience variation in the prevalence of statin side effects due to sociodemographic, behavioral, and/or biological factors. Therefore, identifying the most impactful determinants that can be modified to prevent or reduce statin side effects for individuals from high-risk ethnic minority groups, such as NHOPI, can lead to more effective strategies to reduce health disparities. Thus, our Mini-Review explores the challenging aspects of public health precise strategies in NHOPI taking statins, including a culturally informed additional therapy that could positively impact the NHOPI population.